ANALISIS WANPRESTASI PROMOTOR KONSER DAY6 DAN PERLINDUNGAN KONSUMEN DALAM PERSPEKTIF HUKUM PERDATA - Fayruz Khalisa Fatin (Jurnal Dialektika Hukum, 2025)
Indonesia is one of the countries that often holds music concerts. One example of a music concert that is popular among teenagers today is the Korean pop music (K-Pop) concert. However, in its implementation, it is not uncommon for a concert to cause legal problems, one of which is the breach of contract by the concert promoter that harms consumers. This article aims to analyze Mecimapro's responsibility as the promoter of the DAY6 concert in civil law for the losses suffered by consumers due to the concert promoter's failure to fulfill its obligations. The research method used is normative juridical with a legislative approach and literature study. The results of the analysis show that the agreement between the promoter and consumers through the purchase of tickets is an agreement based on mutual consent, as stipulated in the Civil Code. If the promoter fails to fulfill their obligations, they can be considered in breach of contract and are obliged to provide compensation to consumers. In addition, Consumer Protection Law Number 8 of 1999 also serves as the legal basis for consumers to claim compensation. Thus, the concert promoter Mecimapro, as a business entity, is civilly liable to provide compensation and fulfill the rights of consumers who have been harmed.